Identification of biological properties in organismsusing Machine Learning techniques on wholegenome sequences - Ferella, Nicolas (2023)
The advance in technology and genome sequencing processes in the recentdecades have made large volumes of biological data available to researchers fromall over the world, which, due to the large scales, are difficult to analyze in theirentirety. Therefore, it is intuitive to think of Artificial Intelligence to work withsuch information.In order to reduce the existing gap between the researchers and the ArtificialIntelligence tools, a software was developed that allows the creation of a works-pace for biological organisms, the processing of its corresponding genomes, andthe creation and training of models of Machine Learning, everything using asimple (yet powerful) graphical interface.The trained models are then analyzed to find which patterns determine theresult of the property that is being investigated on the biological organism,finding in the process the genes with the greatest impact on the model’s predic-tions, allowing the researcher to subsequently analyze the desired genes in thelaboratory, saving time and resources in the process